PENERAPAN DATA MINING DATA LOAN SYSTEM PADA PT.FINANCE MENGGUNAKAN METODE KLASTERING (Information Technology and Telematics, 2015)
Abstract-The Subdiniving for number of loan system datas was acquired by sum of the branch offices proffering to the head office. In case of that proffering, the head office will be able to analyse of what branch offices mistake did. The application that’s used is mining datas clustering method which could classify loan datas system based on the number of proffering each mont or year. The valid datas that is utilized are branch offices datas from January to December 2014. which used Allogaritm K-Means for analyzing, visual basic 6 for software and MySQL for data base. According to the analyzing, an application mining datas could be built to create a subdivining of load datas system based on the proffering. Hope that this application is effective for company in decision making as simple as possible. Keywoard: Mining datas, Clustering, Algoritma Allogaritm K-Means, VB.NET 6, MySQL